ANALISIS PENGANGGURAN DALAM MENINGKATKAN RISIKO KEMISKINAN MASYARAKAT - Tara Azhari; Hendra Riofita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Unemployment is one of the primary problems in the economy that has a significant impact on the poverty level of society. This study aims to analyze how unemployment can increase the risk of poverty and to identify the factors influencing this relationship. The method used is a descriptive qualitative approach with a literature study from various scientific sources. The results show that unemployment directly contributes to declining public income, low purchasing power, and limited access to education and health. In addition, unemployment also creates social inequality and reinforces the cycle of poverty that is difficult to break. Therefore, comprehensive policies are required to reduce unemployment and suppress poverty rates sustainably.